Personal Reflections on Tlingit Men and Matriculture: Transcript - Káakh’utxhéich, Kai Monture (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2025)
In this recorded interview, Kai Monture, Káakh’utxhéich, shares his thoughts about being a Tlingit man and what this means, as well as exploring the role of Tlingit men in the lives of Tlingit women. Transcript available (see PDF).LINK TO VIDEO INTERVIEW: Personal Reflections on Tlingit Men and Matriculture, Kai Monture, Káakh’utxhéich